Strategi Guru dalam Melaksanakan Penilaian untuk Menjamin Keakuratan Hasil Belajar Siswa pada Pembelajaran Seni Budaya (Tari) di Kelas VII SMP Negeri 5 Kerinci - Handayani, Bella Fitri; Indrayuda, Indrayuda (YASIN, 2024)
The covid-19 pandemic that occurred has hit all sectors in the life of the nation and state. The education sector is no exception. The hope that the development of education, which was initially echoed, would continue to advance in the coming years, immediately disappeared. The quality of education seems to have reversed course to a path of great decline, along with slowing economic growth and the outbreak of social problems in society. Likewise at SMP Negeri 5 Kerinci, there was a change in the learning system during the pandemic from online to offline again, a change in the assessment implementation system from online to offline again and a new strategy to be implemented by the Cultural Arts teacher to assess student learning outcomes then the teacher carried out the exam with an offline system but there was not enough time. The purpose of this study is to describe the teacher's strategy in carrying out assessments to ensure the accuracy of student learning outcomes in cultural arts learning (dance) in class VII SMP Negeri 5 Kerinci. The type of research is qualitative research with a case study design. The object of research or research target studied is the strategy of assessing student learning outcomes carried out by teachers in cultural arts learning (dance) in the online / offline learning system which can ensure the accuracy and accuracy of student learning outcomes in class VII SMP Negeri 5 Kerinci in the even semester of the 2020/2021 school year. Based on the results of the research, Cultural Arts Learning at SMP Negeri 5 Kerinci takes place with a Hybrib Learning system where this learning still holds face-to-face meetings with a two-shift system with health protocols, but with limited time subject teachers use textbooks to study then synchronize through face-to-face at school. Based on the results of the analysis, the highest level of accuracy in Dance learning lies in the assessment of skills by using a performance assessment system, performance assessment is a strategy used by Cultural Arts (Dance) teachers in Class VII which can be said to be accurate and guaranteed by the teacher's readiness to make instruments and assessment weights on practical exams.